The Influence of Growth Milk Consumption on Nutritional Status, Illness Incidence, and Cognitive Function of Children Aged 2–5 Years - Dian Novita Chandra; Kinandra R. K. Rambey; Ifana Aprilliyani; Luthfi Saiful Arif; Rini Sekartini (Children)
Background: Adequate nutrition in early childhood is crucial for growth and development. Growth milk, a fortified milk product, has been suggested to address nutritional gaps, but its effectiveness remains uncertain. Methods: This clustered randomized controlled trial aimed to assess the effects of growth milk on the nutritional status, immune resilience, appetite, and cognitive function of children aged 2–5 years in Kampung Melayu, East Jakarta. The intervention lasted three months, with 49 participants from two clusters being randomly assigned to either the intervention group or the control group. Nutritional status was assessed monthly. Illness incidence, appetite, food fussiness, and cognitive function were assessed at baseline and endline. Results: Children in both groups showed significant improvements in weight, height, and head circumference growth. Significant height differences between the groups was found, although considered minimal clinically. The height-for-age Z-scores significantly increased from −1.65 to −1.58 only in the intervention group, suggesting the positive effects of growth milk supplementation on children’s growth. No significant differences were observed between the groups pertaining to illness incidence, appetite, food fussiness, and cognitive function. Both groups exhibited similar levels of appetite and reported similar cognitive development outcomes. Conclusions: Growth milk supplementation resulted in improved growth parameters in children; however, it showed the same trend in the growth milk and the control group. No changes in illness incidence and cognitive development were observed in both groups. Longer studies and the inclusion of malnourished children may provide a better understanding of the broader benefits of growth milk supplementation.